+0  
 
0
37
1
avatar

sqrt(-36)^3 = -216i 

 

Can someone expain to the steps to this problem?

Thank you. smiley

Guest Aug 19, 2017
Sort: 

1+0 Answers

 #1
avatar
0

sqrt(-36)^3 =  You can write it like so:

 

sqrt(-1)^3 x sqrt(36)^3     =

sqrt(-1)^3 x           6^3      = 

  i^3           x          216      =

[-1 x i]       x           216      =

-i                x           216     = - 216i

Guest Aug 19, 2017

10 Online Users

avatar
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details